5 A hybrid approach using pulse field ablation and three-dimensional mapping in atrial fibrillation ablation: a relatively early worldwide experience. (6th October 2022) - Mittal, A; Hong, K; Fitzpatrick, N; O'Brien, J; Jauvert, G; Keelan, E; Galvin, J; Szeplaki, G; Boles, U
Abstract : Background and Aim: Pulmonary vein (PV) isolation via thermal ablation remains the cornerstone of atrial fibrillation (AF) treatment. However, both cryoablation and radiofrequency ablation are limited by tissue non-selectivity, collateral damage to surrounding structures (oesophagus and/or phrenic nerve), procedural time and additional parameters (stability, contact force) to achieve optimal lesion quality. Pulse field ablation (PFA) has emerged as a novel nonthermal ablative modality which selectively ablates myocardial tissue within a few seconds and with minimal effect on surrounding tissues. While PFA has been associated with high success rates and decreased procedural times, substantially larger wide antral circumferential lesions have frequently been observed, raising the concern of compromised left atrial (LA) volumes and systolic function post-PVI. Furthermore, the lack of three-dimensional (3-D) data excludes the importance of voltage criteria in confirming bidirectional block and PV isolation. Methods and Procedures: Herein, we present cases from our early series of AF patients treated with a hybrid PFA and 3D-mapping approach. A multicomponent system was utilized: i) FARASTAR™, a custom PFA Generator producing therapeutic biphasic waveforms in microsecond scale pulses ii) FARAWAVE™, (Farawave, Farapulse, Inc., Menlo Park, CA, USA), a 31mm Penta spline, multielectrode, variable deployable flower/basket catheter iii) FARADRIVE ™, a 16.8F steerable sheath. Electroanatomic maps were created using the CARTO Module3 navigation system with integrated CARTOUNIVU and OCTARAY™ mapping catheter (Biosense Webster, Irvine, CA). This hybrid approach allowed for optimal positioning of the Farawave catheter at the PV antrum (PVOs) via direct visualization. Current guidelines recommend the use of PFA to target each PV with 8 applications (basket and flower configuration), each lasting 2 seconds with a generator charging time of 6–8 seconds in between intervals. PFA using a 31-mm FARAWAVE with a single transseptal approach was employed. The successful isolation of all 4 PVs was achieved under fluoroscopy and CARTO guidance with more accurate visualization of the anatomical location and ablation catheter on 3D mapping ( figure 1A and 3 ). Wide antral circumferential ablation (WACA) was confirmed with remapping and multisite pacing documenting bi-directional block across both WACA lines ( figure 2A and 1C ). Results: In the studied example, 3-D high density mapping revealed scarring in the posterior wall with complex fractionated atrial electrograms (CFAEs) before PVI starts. Posterior wall isolation was achieved with 4 applications delivered in the flower-like shape ( figure 1B ) and bidirectional block was demonstrated via remapping using voltage guided criteria (i.e., scar tissue voltages ≤ 0.5 mV) and multisite pacing across the ablated posterior wall. Using voltage criteria, the distance between the boundary of the WACA line to PVOs was delineated and were in the range of 12 mm to 17.2 mm and distance between right and left WACAs was 10mm ( figure 2A ). Conclusions: We report relatively early clinical evidence for the use of combined PFA ablation and 3-D mapping in achieving higher success rates, procedural safety, and efficacy. The combined approach utilized 3-D mapping; hence demonstrating the use of voltage criteria to anatomically optimize outcomes with minimal LA scarring and to confirm bidirectional block of PV potentials.